2007
DOI: 10.1016/j.jcrs.2006.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Intacs for the correction of keratoconus: Two-year follow-up

Abstract: Intacs implantation was a safe and efficacious treatment for keratoconus. Significant and sustained improvements in objective visual outcomes were achieved in most cases, with restoration of contact lens tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 15 publications
1
61
0
2
Order By: Relevance
“…Intracorneal ring segments were implanted horizontally in the studies by Colin et al 35 and Boxer Wachler et al 17 Kanellopoulos et al 36 used a modified nomogram with asymmetric insertion as follows: For an SE less than À2.00 D, a combination of a 0.25 mm segment superiorly and 0.35 mm segment inferiorly was used; for an SE from À2.00 to À3.00 D, a combination of a 0.25 mm segment superiorly and 0.40 mm segment inferiorly was used; for an SE from À3.00 to À5.00 D, a combination of a 0.25 mm segment superiorly and 0.45 mm segment inferiorly was used; for an SE from À5.00 to À6.00 D, a combination of a 0.35 mm segment superiorly and 0.45 mm segment inferiorly was used;…”
Section: Implantationmentioning
confidence: 99%
“…Intracorneal ring segments were implanted horizontally in the studies by Colin et al 35 and Boxer Wachler et al 17 Kanellopoulos et al 36 used a modified nomogram with asymmetric insertion as follows: For an SE less than À2.00 D, a combination of a 0.25 mm segment superiorly and 0.35 mm segment inferiorly was used; for an SE from À2.00 to À3.00 D, a combination of a 0.25 mm segment superiorly and 0.40 mm segment inferiorly was used; for an SE from À3.00 to À5.00 D, a combination of a 0.25 mm segment superiorly and 0.45 mm segment inferiorly was used; for an SE from À5.00 to À6.00 D, a combination of a 0.35 mm segment superiorly and 0.45 mm segment inferiorly was used;…”
Section: Implantationmentioning
confidence: 99%
“…The most current are corneal collagen crosslinking (CXL) with riboflavin and ultraviolet light [4][5][6][7] and implantation of intrastromal corneal ring segments (ICRS). 2,3,[8][9][10][11][12][13][14] However, corneal grafting remains the definitive option, [15][16][17] and deep anterior lamellar keratoplasty is the preferred grafting technique. [18][19][20] Corneal CXL is used to halt ectasia progression, [4][5][6][7] whereas ICRS implantation is used to improve refraction.…”
mentioning
confidence: 99%
“…We found that the preoperative keratometry values were higher in our study when compared with similar studies. [20][21][22] Moreover, the preoperative UDVA and CDVA were worse in our study. This can be explained by the behavior of keratoconus in some children, which can rapidly evolve, and when the surgery is indicated the disease is more advanced.…”
Section: Discussionmentioning
confidence: 39%